Two variants in the fibulin2 gene are associated with lower systolic blood pressure and decreased risk of hypertension. - Joan-Carles Vallvé (Public Library of Science (PLoS), 2012)
Arterial stiffness is an important factor in hypertension. Fibulin 2 is an extracellular matrix scaffold protein involved in arterial stiffness and, hence, the fibulin 2 (FBLN2) gene may be a candidate for hypertension susceptibility. 4 single nucleotide polymorphisms (SNPs) of FBLN2 were evaluated in an association case-control study containing 447 hypertensive patients and 344 normotensive control subjects. The minor allele frequencies of rs3732666 and rs1061376 were significantly lower in hypertensives. The odds ratios (OR) for having the protective G (rs3732666) and T (rs1061376) alleles were 0.75 (95%CI: 0.58 to 0.96) and 0.83 (95%CI: 0.66 to 1.02), respectively. For rs3732666, the OR for hypertension in AG+GG subjects, compared with AA, was 0.71 (95%CI: 0.52 to 0.95). The protective genotype AG+GG was associated with significantly lower systolic blood pressure (SBP) [-3.6 mmHg (P = 0.048)]. There was a significant age interaction with rs3732666; the effect decreasing with increasing age. For rs1061376, TT subjects had an OR for hypertension of 0.53 (95%CI: 0.32 to 0.87) compared with CC subjects, with reduced SBP (-7.91 mmHg; P = 0.008) and diastolic BP (DBP) (-3.69 mmHg; P = 0.015). The presence of a G allele was an independent predictor of intima-media thickness (IMT); G carrier's having lower mean IMT (-0.037 mm, P = 0.027) compared with AA. Our results provide the first evidence for FBLN2 as a new gene associated with hypertension.